Aspergillus coinfection among patients with pulmonary tuberculosis in Asia and Africa countries; A systematic review and meta-analysis of cross-sectional studies. (April 2020) - Hosseini, Motaharesadat; Shakerimoghaddam, Ali; Ghazalibina, Mehran; Khaledi, Azad
Abstract: Progress of the disease and prolonged treatment with antibiotics or immunosuppressive agents makes tuberculosis patients susceptible to fungal infections. This study aimed to determine the prevalence of pulmonary Aspergillus coinfection among patients with pulmonary tuberculosis in Asia and Africa. The present review of cross-sectional studies was conducted on the prevalence of pulmonary Aspergillus coinfection among patients with pulmonary tuberculosis according to the PRISMA Protocol. Literatures published online in English from January 2001 to March 2019 via key databases such as Web of Science, MEDLINE, PubMed, Scopus, and Cochrane Library were searched. The used MeSH and non-MeSH keywords were; "pulmonary fungal", "pulmonary coinfection", OR "Pulmonary mycosis", "pulmonary fungal infections/agents", OR "Polymicrobial infection", OR "Secondary infection", OR "Mixed infections", "pulmonary aspergillosis", "fungi coinfection", "Fungal co-colonization", AND "pulmonary tuberculosis", OR "pulmonary TB", AND "Asia" AND "Africa". Finally, data analyzed using Comprehensive Meta-Analysis software (CMA). The combined Aspergillus coinfection among patients with pulmonary tuberculosis was 15.4% (95% CI: 11.4–20.5), Q = 105.8 and Z = 9.57 in Asia and Africa. The most frequency of Aspergillus spp. was related to A. fumigatus with a combined prevalence of 57.6%. Most of the studies included in the present review showed a higher Aspergillus coinfection in the age group of 40 years and higher. Also, the existence of a correlation between increasing age and Aspergillus coinfection was reported (p < 0.05). The present review showed a high combined Aspergillus coinfection among patients with pulmonary tuberculosis in Asia and Africa. Also, amongst the Aspergillus spp., the most frequent was related to A. fumigatus . Highlights: The combined Aspergillus coinfection among patients with pulmonary tuberculosis was 15.4% in Asia and Africa. The most frequency of Aspergillus spp. was related to A. fumigatus with a combined prevalence of 57.6%. Also, the existence of a correlation between increasing age and Aspergillus coinfection was reported.